2015
DOI: 10.1371/journal.pone.0117193
|View full text |Cite
|
Sign up to set email alerts
|

African Baobabs with False Inner Cavities: The Radiocarbon Investigation of the Lebombo Eco Trail Baobab

Abstract: The article reports the radiocarbon investigation results of the Lebombo Eco Trail tree, a representative African baobab from Mozambique. Several wood samples collected from the large inner cavity and from the outer part of the tree were investigated by AMS radiocarbon dating. According to dating results, the age values of all samples increase from the sampling point with the distance into the wood. For samples collected from the cavity walls, the increase of age values with the distance into the wood (up to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 19 publications
0
70
0
Order By: Relevance
“…A study sampling wood from different aspects of a baobab tree with false cavities from Mozambique reveals that extant portions of the tree can be >1,300 years old (Patrut et al 2011;Patrut et al 2015). The study showed that single baobab trees can yield radiocarbon ages separated by hundreds of years, depending on the aspect of the tree that is sampled.…”
Section: Old Woodmentioning
confidence: 98%
“…A study sampling wood from different aspects of a baobab tree with false cavities from Mozambique reveals that extant portions of the tree can be >1,300 years old (Patrut et al 2011;Patrut et al 2015). The study showed that single baobab trees can yield radiocarbon ages separated by hundreds of years, depending on the aspect of the tree that is sampled.…”
Section: Old Woodmentioning
confidence: 98%
“…Then, CO 2 was reduced to graphite on iron catalyst, under hydrogen atmosphere. Finally, the resulting graphite samples were analysed by AMS [4,18,19].…”
Section: Sample Preparationmentioning
confidence: 99%
“…The research is based on our approach which also allows to investigate and date standing and live specimens. This approach involves the AMS radiocarbon dating of small wood samples collected from inner cavities and/or from deep incisions/entrances in the stems, fractured stems and from the outer part/exterior of large baobabs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…We documented the open and closed ring-shaped structures, which are the most important architectures that enable African baobabs to reach old ages and large sizes. We also identified the presence of false cavities, which are large natural empty spaces between several fused stems disposed in a closed ring-shaped structure, which have never been filled with wood [9][10][11][12][13]. The oldest dated A. digitata specimens were found to have ages greater than 2000 yr [14,15].…”
Section: Introductionmentioning
confidence: 99%